Vielleicht ein Projekt? - HOFFMANN, Marta (Wydawnictwo Naukowe UAM, 2000)
With the new school reform on the high school level teachers should aim at the students global development (students should not leam for school purposes but rather for life). A helping form in this kind of teaching may be a given project which in this article is explained as a whole.